2020
DOI: 10.1080/21645515.2019.1674598
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, knowledge, and willingness to be vaccinated against seasonal influenza among patients hospitalized with influenza-like-illness: impact of diagnostic testing

Abstract: Attitudes, knowledge, and willingness to be vaccinated against seasonal influenza among patients hospitalized with Influenza-Like-Illness: impact of diagnostic testing Sarah Tubiana (ST) a,b Odile Launay (OL) c,d,e , Florence Galtier (FG) e,f , Pierre Tattevin (PT) e,g , Deborah Postil (DP) e,h , Philippe Vanhems (PVA) e,i , Nezha Lenzi (NL) e , Pierre Verger (PVE) e,j,k , Xavier Duval (XD) a,b,e and the Fluvac Study group a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Individuals with higher levels of willingness to take a rapid test may have higher levels of intent to avoid being infected by COVID-19. This finding echoes prior evidence in the relationship between willingness to get influenza vaccinated and diagnostic testing [ 52 ]. Therefore, willingness to take a rapid test is a good predictor of COVID-19 vaccination uptake willingness.…”
Section: Discussionsupporting
confidence: 85%
“…Individuals with higher levels of willingness to take a rapid test may have higher levels of intent to avoid being infected by COVID-19. This finding echoes prior evidence in the relationship between willingness to get influenza vaccinated and diagnostic testing [ 52 ]. Therefore, willingness to take a rapid test is a good predictor of COVID-19 vaccination uptake willingness.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, our multifaceted intervention significantly increased influenza vaccination uptake whereas half of the participants reported being previously vaccinated against influenza. We previously found that history of seasonal influenza vaccination was associated with willingness to be vaccinated [ 25 ]. Participants in our study were not previously vaccinated against pneumococcal and therefore might be less prone to vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Paramivir is a new inhibitor, which can effectively inhibit the activity of neuraminidase, and then inhibit the bond breakage between viral hemagglutinin and sialic acid of infected cells, thus preventing the release of virus and reducing clinical symptoms [9,10] . [11][12][13] .…”
Section: Groupsmentioning
confidence: 99%